Modular Modelling Analysis of the o-, m- and p-Directing Influences of Substituents in Electrophilic Attack on Aromatic Compounds - HUQ, FAZLUL (Asian Journal of Chemistry, 2010)
Molecular modelling analyses using molecular mechanics, semiempirical, DFT and ab initio calculations were carried out to investigate the effect of substituents in electrophilic substitution in benzene derivatives. The results of calculations show that the ortho-, meta- and para-directing influences of substituents in electrophilic attack are governed by the net atomic charges rather than relative stability of the resulting isomers.